2022
DOI: 10.1578/am.48.5.2022.449
|View full text |Cite
|
Sign up to set email alerts
|

Stomach Contents of Three Sperm Whales (Physeter macrocephalus) Stranded on Andøya, Northern Norway

Abstract: Three male sperm whales (Physeter macrocephalus) stranded on the island of Andøya in northern Norway in 2020. This created an opportunity to do gross necropsies with a focus on stomach contents as the diet of sperm whales in Norwegian waters is poorly understood and also to study potential presence of marine debris. Four new prey types for sperm whales in Norwegian waters were identified: (1) angler fish, (2) Atlantic cod, (3) cartilaginous fish, and (4) cock-eyed squid. In general, the results support earlier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Sperm whale diet is believed to mainly consist of cephalopods and fish, but there is regional variation. Boreoatlantic armhook squid ( Gonatus fabricii) has been identified as an important prey species in the North Sea 59 and Northern Norway 60 and this potential prey species does range up to northern Svalbard (Atwain). High concentrations have been reported around the Eastern Fram Strait site 61 which is also a suspected spawning site for these squid 62 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sperm whale diet is believed to mainly consist of cephalopods and fish, but there is regional variation. Boreoatlantic armhook squid ( Gonatus fabricii) has been identified as an important prey species in the North Sea 59 and Northern Norway 60 and this potential prey species does range up to northern Svalbard (Atwain). High concentrations have been reported around the Eastern Fram Strait site 61 which is also a suspected spawning site for these squid 62 .…”
Section: Discussionmentioning
confidence: 99%
“…MacKenzie et al 63 concluded based on their stable isotope analyses that sperm whales likely consume deep-water species such as squid. Fish species such as the lumpsucker ( Cyclopterus lumpus ) and Atlantic cod ( Gadus morhua ) have also been found to be part of sperm whale diet in the North Atlantic 60 , 64 and these fish species are also found in the Eastern Fram Strait and off the west coast of Spitsbergen 65 , 66 . At Eastern Fram Strait, sperm whale presence peaked shortly after the peak in zooplankton concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the killer whale, sperm whale and longfinned pilot whale had the lowest concentrations of phthalates compared to the white-beaked dolphin, harbour porpoise and harbour seal. Whilst information about their diet is not available in the literature for all the species in this study area, it is known that killer whales off the Norwegian coast eat a range of prey including (primarily) herring, but also other fish and marine mammal prey (Jourdain et al, 2019), and that sperm whales from Norway and long-finned pilot whales from the North Atlantic feed on deep-sea benthic prey (Christensen et al, 1992;Desportes and Mouritsen, 1988;Mendes et al, 2007;Similä et al, 2022). The stable isotope ratios of nitrogen in sperm whales were higher than baleen whales in the Barents Sea (Mackenzie et al, 2022), and there are indications that they are high trophic species due to the trophic level of their prey being comparable to top vertebrate predators in the Arctic (Golikov et al, 2018).…”
Section: Discussionmentioning
confidence: 99%